2018
DOI: 10.1371/journal.pone.0190860
|View full text |Cite
|
Sign up to set email alerts
|

A purified, fermented, extract of Triticum aestivum has lymphomacidal activity mediated via natural killer cell activation

Abstract: Non-Hodgkin lymphoma (NHL) affects over 400,000 people in the United States; its incidence increases with age. Treatment options are numerous and expanding, yet efficacy is often limited by toxicity, particularly in the elderly. Nearly 70% patients eventually die of the disease. Many patients explore less toxic alternative therapeutics proposed to boost anti-tumor immunity, despite a paucity of rigorous scientific data. Here we evaluate the lymphomacidal and immunomodulatory activities of a protein fraction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…After duplicates were removed, 20 studies were identified as acceptable for full-text evaluation and their full texts were read. At the end of the selection process, 16 articles [ 13 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] were included in qualitative analysis, while four [ 9 , 17 , 35 , 36 ] were excluded for not complying with inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After duplicates were removed, 20 studies were identified as acceptable for full-text evaluation and their full texts were read. At the end of the selection process, 16 articles [ 13 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] were included in qualitative analysis, while four [ 9 , 17 , 35 , 36 ] were excluded for not complying with inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…All sixteen studies selected for the review were in-vitro studies published in English. The effects of FWGE were investigated on the following cell lines: Jurkat leukemic T cells were studied by three studies [ 18 , 21 , 32 ] and the treatment resulted in cytotoxic effects, alteration of the cell cycle, antiproliferative effects, and induction of apoptosis; Lymphoma cells were subjected to the treatment and the effects investigated by three studies [ 21 , 27 , 32 ] showed growth inhibition, induction of apoptosis, antiproliferation, and cytotoxic effects; Gastric cancer cell line experiments reported in three papers [ 22 , 25 , 26 ] found antiproliferative, cytotoxic, cytostatic, and growth-delay effects; Ovarian cancer cell lines, when subjected to treatment with AVEMAR, showed cytotoxic effects [ 23 ], antiproliferative activity [ 25 ], and suppression of cell proliferation [ 29 ]; Breast cancer cell lines appeared to undergo cytotoxicity and apoptosis [ 24 , 25 , 26 , 32 ], while, in one study [ 33 ] investigating the combined administration of AVEMAR and cytostatics, the treatment with AVEMAR resulted in no increase or decrease of cell viability compared to untreated cells; When applied to colon cancer cell lines, FWGE showed antiproliferative activity [ 25 ], cytotoxicity, cytostasis, and induction of cell apoptosis [ 31 ]; The treatment of hepatic cancer cells appeared to cause cytotoxicity, apoptosis [ 32 ], and an inhibition of proliferation [ 25 , 28 ]; Other types of cell lines investigated in the included studies were prostate cancer cells, endocervical adenocarcinoma [ 22 ], cervical epidermoid carcinoma cells [ 25 ], testicular cancer cell lines [ 25 ], head and neck cancer [ 25 ], thyroid and pancreatic cancer cells [ 13 ], melanoma, hepatoma, glioblastoma, neuroblastoma [ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, plant protein extracts could potentially be further processed to added-value products or pharmaceuticals [171,172], and fermentation processes may serve as instruments to increase tailored health-supporting bioactivities. As an example, a wheat germ protein extract fermented with baker's yeast has been found effective in reducing tumors related with non-Hodgkin lymphoma in an immunodeficient mouse model, probably via a natural killer cell regulated antitumor mechanism [173].…”
Section: From In Vitro To In Vivomentioning
confidence: 99%